The overall dance of specialised translation - Maria Cecília Basílio (JoSTrans: The Journal of Specialised Translation)
Integrating insights from disciplines with relevance to translation theory, namely David Bohm's theory of wholeness, Michael A.K. Halliday's "functional grammar", Peter Newmark's communicative and semantic translation polarity, and Jacques Derrida's "deconstruction" (as reading practice), I focus on an understanding of "specialised translation" as enfolding the translator's awareness of discourse as a meaning creation process, together with his ability to "think grammatically" in order to "act grammatically" in the process of reading and translating both literary and non-literary texts of quality.